Експресивність реабілітуючих ефектів омега-3 поліненасичених жирних кислот у хворих на цукровий діабет 2-го типу з поліморфними варіантами гена параоксонази - Горшунська, М. Ю.; Караченцев, Ю. І.; Кравчун, Н. О.; Йенсен, Е.; Атраментова, Л. О.; Гладких, О. І.; Красова, Н. С.; Лещенко, Ж. А.; Тижненко, Т. В.; Опалейко, Ю. А.; Почерняєв, А. К.; Полторак, В. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
The paper presents data on the basis of which it is firstly proved the role of Q192R genetic variants of the paraoxonase gene (PON1) in the formation of the therapeutic efficacy of omega-3 polyunsaturated fatty acids (Omacor medicine) in patients with type 2 diabetes in relation to new cardiovascular risk factors (insulin resistance, adipocytokines, antioxidant protection) with the identification of QQ genotype as the most reactive. The results confirm the promise of pharmacogenetics as a basis for personalized therapy with a predicted effect of pharmacological intervention.